Molecular phylogeny and morphology reveal a new species of Gloeocystidiellum (Stereaceae, Russulales) from Southwestern China - Zhu, Yajuan; Dong, Junhong; Shen, Kaize; Yang, Shunqiang; Zhao, Changlin; Zhan, Zhongyi (Phytotaxa, 2025)
Gloeocystidiellum yaoshanense sp. nov., found in Yunnan Province, Southwestern China, is described here as a new species based on its morphology and phylogenetic analyses. Gloeocystidiellum yaoshanense is characterized by its membranaceous basidiomata with cracked, grandinioid hymenial surface, a monomitic hyphal system bearing simple septa on generative hyphae, and broadly ellipsoid to ellipsoid basidiospores measuring 4–4.6 × 3–3.5 µm. Phylogenetic analyses of the new species were carried out based on the nuclear ribosomal internal transcribed spacer (nrITS) and the nuclear large subunit (nrLSU) of ribosomal DNA. The phylogenetic analyses indicated that the new species belongs to the genus Gloeocystidiellum and forms a monophyletic lineage. A full description, illustrations, and phylogenetic analysis results of the new species are provided.